Relative Frequency of Islet Autoimmunity in Children and Adolescents with Autoimmune Thyroid Disease - Natasa Rojnic Putarek; Nevena Krnic; Jadranka Knezevic-Cuca; Vesna Kusec; Maja Baretic; Miroslav Dumic (Galenos Yayincilik, 2023)
INTRODUCTION: The aim of the present study was to investigate islet autoimmunity and susceptibility to type 1 diabetes (T1D) in children/ adolescents with autoimmune thyroid disease (AITD, and in family members of AITD patients with islet autoimmunity. METHODS: Islet-cell cytoplasmic, glutamic-acid decarboxylase, and tyrosine-phosphatase autoantibodies (AAbs) were measured in 161 AITD patients [127 with autoimmune thyroiditis (AT); 34 with Graves' disease (GD)], 20 family members of AITD patients with islet autoimmunity, and 155 age-matched controls. RESULTS: Islet autoimmunity was found in 10.6% of AITD patients, significantly more frequent than in controls (1.9%; p=0.002). A higher prevalence of islet AAbs was found in females with AITD (p=0.011) but not in males (p=0.16) and in AT (p=0.013) but not in GD patients (p=0.19), compared to corresponding controls. Two or three islet AAbs were found concurrently in six AITD patients with islet autoimmunity. They all developed T1D and had significantly higher islet AAbs titers (p=0.01) than AITD patients with single islet AAbs but normal glucose metabolism. T1D was found in 3.7% of AITD patients compared to 0.2% of the age-matched, general Croatian population. Islet AAbs were found in 5/20 family members of AITD patients with islet autoimmunity, among whom two developed T1D. None of the controls was positive for more than one islet AAb or developed T1D. DISCUSSION AND CONCLUSION: Children/adolescents with AITD, particularly females and patients with AT, appear to represent a risk group for islet autoimmunity and T1D, as do family members of AITD patients with positive islet AAbs. However, these findings should be validated in larger studies.